MENINGKATKAN PERTUMBUHAN TANAMAN MENTIMUN (Cucumis sarivus L.) DI TANAH SALIN DENGAN PELINDIAN TANAH DAN PENAMBAHAN AMELIORAN - Putra, Rafii Adhimas Tri; Bowo, Cahyoadi (Jurnal Tanah dan Sumberdaya Lahan, 2024)
This study aimed to assess the impact of combinations of varying soil amendments and water amounts on the leaching water requirement for cucumber growth and production. Saline soil was collected from Banongan, Situbondo, with soil electrical conductivity (EC) of 4-6 dS m-1. A 10 kg soil sifted with a diameter of 2 mm was placed in each mini lysimeter. Leaching was carried out until the soil EC reached below 2 dS m-1. The results showed that soil leaching reduced soil EC from 5 dS m-1 to 1.6-1.8 dS m-1; meanwhile, EC in leachate ranged from 2-2.3 dS m-1. Biochar treatment caused an increase in leaching water requirements. In addition, applying biochar combined with 40 mm day-1 of water produced the highest fruit number. The combination treatment of cow manure 100 g pot-1 (equivalent to 20 t ha-1) and biochar 30 g pot-1 (equivalent to 6 t ha-1) and adding 40 mm day-1 of water during each water application produced the most prominent fruit volume. Furthermore, utilizing 40 mm day-1 of leaching water produced the best number of leaves, fruit weight, length, and fruit circumference.